Melioidosis as a Cause of Acute Abdomen in Immuno-Competent Male from Eastern India - Karuna, Tadepalli (J Lab Physicians, 2015)
Though melioidosis is rare in India, it has gained importance as one of the most potent emerging infections. In India, the cases have been under-reported because of the lack of awareness. The majority of cases present with multifocal pyogenic infections with septicemia. We present an unusual case of melioidosis presenting as acute intestinal perforation. The organism was ceftazidime resistant, and we successfully treated the case with imipenem and doxycyclin. This case highlights ruling out the possibility of melioidosis in acute abdomen and existence of ceftazidime resistant cases in India.